Pandion haliaetus ... - Bishop, K. David (Zenodo, 2023)
OSPREY Pandion haliaetus # Local name Man Ginin (Sansundi). Range P. h. cristatus Biak, Supiori, Owi, Numfor, Yapen. Status Resident or Palearctic migrant? First noted by Ripley on Supiori in May 1937 (Mayr & Meyer de Schauensee 1939) and collected by Hoogerheide on 8 December 1953 (Junge 1956). Thereafter recorded by most visitors in May‒December. January 1997: singles at Marauw and Sansundi (SvB). During August 2018 and 2019 up to 3‒6 at the tsunami swamp. 13 January 1994: two on Owi (P. Gregory in litt. 2000). Without more information it is impossible to speculate on the origins of these birds. However, P. h. haliaetus has been recorded as a winter migrant on Sulawesi (Coates & Bishop 1997). Breeding 7 July 1982: KDB observed a pair perched atop a tall dead tree above Kuneff, on the south coast of Supiori whose behaviour suggested they may have been looking to nest. ... : Published as part of Bishop, K. David, 2023, The avifauna of Biak Island, Papua, Indonesia with comments on status, conservation, natural history and taxonomy, pp. 3-62 in Bulletin of the British Ornithologists' Club 143 (1) on page 36, DOI: 10.25226/bboc.v143i1.2023.a2, http://zenodo.org/record/11642130 ...